Molecular mechanisms of long noncoding RNAs‐mediated cancer metastasis. Issue 4 (8th February 2019) - Li, Yajuan; Egranov, Sergey D.; Yang, Liuqing; Lin, Chunru
Abstract: Cancer metastasis is a multistep process that requires cancer cells to leave the primary site, survive in the blood stream, and finally colonize at a distant organ. It is the major cause of cancer morbidity and mortality. The organ‐specific colonization requires close interaction and communication between cancer cells and host organs. Noncoding RNAs represent the majority of the transcriptome, with long noncoding RNAs (lncRNAs) making up a significant proportion. It has been suggested that lncRNAs play a key role in all stages of tumorigenesis and metastasis. This review will provide an overview of how lncRNAs are involved in cancer cell colonization in specific organ sites and the underlying mechanisms as well as therapeutic strategies.